Resor Pulau Setanau Pada Gugusan Pulau Tiga Di Natuna Dengan Pendekatan Arsitektur Pesisir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Setanau Island is one island that is unsettled and located at Pulau Tiga Subdistrict, Natuna regency. Setanau Island has the potential to be visited by tourists, both local and foreign tourists. Therefore is needed accommodation tourist activity on the island of Setanau. The concept of Setanau Island Resort was designed by